2016
DOI: 10.4269/ajtmh.15-0505
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Leptospira kirschneri Serovar Mozdok: First Report from the Southern Hemisphere

Abstract: Leptospirosis is a global zoonosis caused by pathogenic Leptospira spp. In this study, we characterized two Leptospira kirschneri serogroup Pomona serovar Mozdok isolates, one obtained from a dog and the other from a patient with severe leptospirosis, 4 years later. Histopathological analysis showed that both isolates caused severe tissue damage when used to infect hamsters. While L. kirschneri serogroup Pomona serovar Mozdok is endemic in animals in Europe, there is only one report of human leptospirosis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
1
21
0
2
Order By: Relevance
“…Classically, L. interrogans serovars, especially Canicola have been associated with asymptomatic renal carriage in dogs [32]. However, multiple studies have recovered other leptospiral species from asymptomatic dogs, including L. borgpetersenii, L. kirschneri, L. wolfii, and L. santarosai [33,34,22,35]. In the present study, sequence analysis of PCR-positive dog urine samples revealed that L. interrogans was the species involved in infections.…”
Section: Discussionmentioning
confidence: 54%
“…Classically, L. interrogans serovars, especially Canicola have been associated with asymptomatic renal carriage in dogs [32]. However, multiple studies have recovered other leptospiral species from asymptomatic dogs, including L. borgpetersenii, L. kirschneri, L. wolfii, and L. santarosai [33,34,22,35]. In the present study, sequence analysis of PCR-positive dog urine samples revealed that L. interrogans was the species involved in infections.…”
Section: Discussionmentioning
confidence: 54%
“…Concerning the epidemiology of leptospirosis, there is a lack of information on the countryside areas of Brazil, compared to that on the urban areas where serovars Copenhageni and Icterohaemorrhagiae are predominant 2,5 . However, it should be highlighted that there are reports of other serovars found in different species of domestic and wild animals in those areas 6,7 .…”
mentioning
confidence: 99%
“…Based on the available information, serovar Mozdok is rarely isolated from humans in Brazil 7 . This is only the second report concerning the isolation of L. kirschneri putative serovar Mozdok from a human case in a rural area of Brazil.…”
mentioning
confidence: 99%
“…No entanto, Hartskeerl & Terpstra (1996) já discutiam a existência de variação de hospedeiros de manutenção e respectivos sorovares pelo mundo. A variação de espécies e sorovares de Leptospira nos animais domésticos continua a ser descrita (Lilenbaum et al, 2007;Cunha et al, 2016;Miotto et al, 2016) (Wang et al, 2015). Na África e no sudeste Asiático é descrito predomínio de L. borgpetersenii, L. interrogans e L. kirschneri, tanto em animais quanto em humanos (Desvars et al, 2012;Cosson et al, 2014;Allan et al, 2015 (Vasconcellos et al, 2001;Sarmento et al, 2012;Monte et al, 2015), enquanto que em suínos predomina L. interrogans sorovares Pomona, Icterohaemorrhagie e Tarassovi (Bolin, 1994;Ferreira Neto et al, 1997;Ramos et al, 2006).…”
Section: Epidemiologiaunclassified
“…Na África e no sudeste Asiático é descrito predomínio de L. borgpetersenii, L. interrogans e L. kirschneri, tanto em animais quanto em humanos (Desvars et al, 2012;Cosson et al, 2014;Allan et al, 2015 (Vasconcellos et al, 2001;Sarmento et al, 2012;Monte et al, 2015), enquanto que em suínos predomina L. interrogans sorovares Pomona, Icterohaemorrhagie e Tarassovi (Bolin, 1994;Ferreira Neto et al, 1997;Ramos et al, 2006). No entanto, as espécies L. noguchii e L. kirschneri também já foram descritas no país ocasionando doença em animais e humanos (Silva et al, 2009;Martins et al, 2015;Cunha et al 2016).…”
Section: Epidemiologiaunclassified